2014
DOI: 10.9734/ejmp/2014/9397
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel GABAA Receptor Channel Ligand Derived from Melissa officinalis and Lavandula angustifolia Essential Oils

Abstract: Aims: Melissa officinalis (Mo) and Lavandula angustifolia (La) essential oils and their major constituents ((E) -caryophyllene, caryophyllene oxide, geranyl acetate, linalool, nerol, Oct-1-en-3-ol, 3-Octanone, myrcene, allo-ocimene, p-cymene and α-terpineol) assessed by GC-MS) which are shared by these two essential oils were probed in an attempt to identify the GABA A R ligand(s). [810][811][812][813][814][815][816][817][818] 2014 811 IC 50 of 40 M. Concentrations (0.001 mg/ml) of whole (Mo) were shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…A neurotropic tissue study (Yoo et al, ) reported decreased GABA‐T levels in the dentate gyrus of C57BL/6 J mice, along with an increase in total GABA levels, following extract 50/200 mg/kg daily for 3 weeks. Finally, in radio‐ligand/electrophysiological studies using male Wistar rat cortical cultures in vitro, M. officinalis extract and selected constituents have shown trans‐ocimene inhibited [35S] (TBPS) binding (set radio ligand) at GABA‐A receptor level, in a dose‐dependent fashion (Mahita et al, ), building upon previous similar findings in preclinical investigations (Abuhamdah et al, ; Huang et al, ).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…A neurotropic tissue study (Yoo et al, ) reported decreased GABA‐T levels in the dentate gyrus of C57BL/6 J mice, along with an increase in total GABA levels, following extract 50/200 mg/kg daily for 3 weeks. Finally, in radio‐ligand/electrophysiological studies using male Wistar rat cortical cultures in vitro, M. officinalis extract and selected constituents have shown trans‐ocimene inhibited [35S] (TBPS) binding (set radio ligand) at GABA‐A receptor level, in a dose‐dependent fashion (Mahita et al, ), building upon previous similar findings in preclinical investigations (Abuhamdah et al, ; Huang et al, ).…”
Section: Resultssupporting
confidence: 60%
“…Awad et al (); Awad et al (); Abuhamdah et al (); Huang et al (); Mahita et al (); Raines et al (); Salah and Jager (); Yoo et al ()…”
Section: Resultsmentioning
confidence: 99%
“…M. officinalis has an average height of 30–125 cm and displays ovate, dark-green leaves and white flowers which bloom in the summer [ 9 , 10 ]. M. officinalis has a large use in traditional medicine, food industry, and aromatherapy, due to its fresh smell and its medicinal properties including hypoglycemic, hepatoprotective, antimicrobial, antidepressant, hypnotic, and sedative [ 1 , 11 14 ]. In addition, there are studies that pointed out the cytotoxic effect of lemon balm extract on breast cancer [ 13 ] and colon carcinoma [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…M. officinalis decoctions also showed hepatotoxicity activity with GI 50 greater than 400 µg/mL on fresh porcine liver cells, PLP2 [106]. M. officinalis volatile oil was non-toxic to HEp-2 cells, a human cervical carcinoma cell line at 100 µg/mL [46] but induced a neurotoxicity effect on mixed cortical cell cultures from 16-to 18-day-old rat embryos (Sprague-Dawley strain) at the same concentration via volt aggregated sodium channels [106].…”
Section: Cell-based Toxicitymentioning
confidence: 97%
“…M. officinalis decoctions and hot extract showed an antiproliferative effect on human tumor cell lines, with GI 50 ranging from 51 to 258 µg/mL for breast (MCF-7), non-small lung (NCI-H460), cervical (HeLa), and hepatocellular carcinoma (HepG2) [104] and at a concentration of 500-1000 µg/mL for human colon cancer cell lines DLD-1 HCT116, SW620, HT-29, and inhibited HT-29 cells [105]. M. officinalis decoctions also showed hepatotoxicity activity with GI 50 greater than 400 µg/mL on fresh porcine liver cells, PLP2 [106]. M. officinalis volatile oil was non-toxic to HEp-2 cells, a human cervical carcinoma cell line at 100 µg/mL [46] but induced a neurotoxicity effect on mixed cortical cell cultures from 16-to 18-day-old rat embryos (Sprague-Dawley strain) at the same concentration via volt aggregated sodium channels [106].…”
Section: Cell-based Toxicitymentioning
confidence: 99%